2022
DOI: 10.1155/2022/8392854
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Ischemic Stroke Recurrence Based on COX Proportional Risk Regression Model and Evaluation of the Effectiveness of Patient Intensive Care Interventions

Abstract: With the continuous improvement of medical technology and the aging of the population, the death rate of stroke is gradually decreasing, but the recurrence rate is still high, and the number of recurrences is increasing, resulting in disability and other symptoms, which brings great burden and distress to patients and their families. As the number of strokes increases, neurological impairment becomes more and more severe, affecting patients’ ability to live, socialize, and work, and seriously reducing their qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Apart from the main causes of stroke and existing pathological state, the incidence of stroke and mortality in patients can be signi cantly reduced after taking corresponding secondary prevention measures 11 . Previous studies have also shown that the analysis of clinical history and laboratory data can accurately predict the adverse outcomes of patients who had experienced an IS, and clinical intervention programs for high-risk factors are also practical and effective [12][13][14] . Nearly 20% of the patients in the Chinese community (i.e., this study's population) die within ve years after their rst stroke, and more than 40% relapse within ve years of an IS 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the main causes of stroke and existing pathological state, the incidence of stroke and mortality in patients can be signi cantly reduced after taking corresponding secondary prevention measures 11 . Previous studies have also shown that the analysis of clinical history and laboratory data can accurately predict the adverse outcomes of patients who had experienced an IS, and clinical intervention programs for high-risk factors are also practical and effective [12][13][14] . Nearly 20% of the patients in the Chinese community (i.e., this study's population) die within ve years after their rst stroke, and more than 40% relapse within ve years of an IS 15 .…”
Section: Introductionmentioning
confidence: 99%